Hubungan Tarikan Penampilan Dan Personaliti Dengan Kecenderungan Membisu Dalam Kalangan Pekerja Malaysia Di Organisasi Jerman - Robe’ah Yusuf; Ezhar Tamam; Jusang Bolong; Mohd Nizam Osman (Universiti Sains Islam Malaysia, 2024)
This study aimed to identify the relationship between interpersonal attraction and personality with silence of subordinates in multinational organisation. The subordinates are Malaysian and the immediate superior is a German. Respondents were consisted of 360 subordinates of various positions reporting to an immediate German superior. The interpersonal attraction was measured based on the instrument of The Measurement of Interpersonal Attraction and Homophily, while the silence was measured based on the model of Dinamika Organisasi Membisu. Personalities of the respondents were measured based on The Measurement of Personality and Characteristics to differentiate between extrovert and introvert personalities. The findings of the pilot study showed that the value of Cronbach alpha of interpersonal attraction is .80, personality .78 and .88 for silence. A descriptive statistic analysis namely the frequency and percentage as well as the inferential statistic in the form of Pearson correlation coefficient was used to test the hypothesis of the study at significant level of .05. The findings showed that the interpersonal attraction of superior was able to influence the communication of subordinate-superior. The findings showed that extrovert subordinates had intermediate perceptions through the interpersonal attraction of superior. The findings of silence showed that introvert subordinates tended to show silence towards the superior in various situations. This matter can be identified based on the results of t-test sample for silence (t (358) = 2.69, p <0.05). This situation showed that, the introvert subordinates were more likely to show silence compare to the extrovert subordinates.